Comparable Effects of Brief Resistance Exercise and Isotime Sprint Interval Exercise on Glucose Homeostasis in Men - Tomas K. Tong; Zhaowei Kong; Xueying Shi; Qingde Shi (Journal of Diabetes Research)
This study compared the effects of a single bout of resistance exercise (RES) on glycemic homeostasis to isotime sprint interval exercise (SIE) using a within-subjects design. Nineteen nondiabetic males (age: 23.3±0.7 yrs; height: 173.1±1.2 cm; weight: 79.1±4.8 kg; % fat: 22.5±2.5%) were studied. RES involved nine exercises of 10 repetitions at 75% 1-RM using a 2 : 2 s tempo and was interspersed with a one-minute recovery; SIE involved four 30 s’ all-out cycling effort interspersed with four minutes of active recovery. Plasma glucose and insulin in response to a 75 g oral glucose tolerance test were assessed 12 h after exercise. In comparison to a no exercise control trial (CON), the area under curve (AUC) of plasma glucose was reduced with both RES and SIE (P<0.05), while insulin AUC was only reduced with RES. Cederholm, Gutt, Matsuda, and HOMA indices were improved (P<0.05) following RES compared to CON. Corresponding changes following SIE were only found in Cederholm and Gutt indices (P<0.05). No difference was found in plasma variables and indices between RES and SIE (P>0.05). Such findings suggest that the RES may represent a potential alternative to the SIE in the development of time-efficient lifestyle intervention strategies for improving diabetes risk factors in healthy populations.